Immunohistochemical mapping of neurotensin in the alpaca diencephalon - Sánchez M.L. (2018)
Introduction. The distribution of the immunoreactive cell bodies and fibers containing neurotensin in the alpaca diencephalon was determined by an immunohistochemical technique. Material and methods. The study was carried out in four male alpacas that lived at sea level. Brains of deeply anesthetized animals were fixed by perfusion with 4% paraformaldehyde. Cryostat sections were stained by a standard immunohistochemical method. Results. Cell bodies containing neurotensin were observed in the zona incerta and hypothalamus. A low/moder-ate density of these cell bodies was observed in the lateral hypothalamic area, anterior and dorsal hypothalamic areas, suprachiasmatic nucleus, periventricular region of the hypothalamus and in the ventromedial hypothalamic nucleus. In both thalamus and hypothalamus, immunoreactive fibers showed a widespread distribution. In the thalamus, a high density of these fibers was mainly found in the midline nuclei, whereas in the hypothalamus a high density was in general observed in the whole structure. Conclusions. In comparison with other mammals, the thalamus of the alpaca showed the most widespread distribution of neurotensin-immunoreactive fibers. The widespread distribution of neurotensin through the alpaca diencephalon suggests that the peptide can be involved in many physiological actions. © Polish Society for Histochemistry and Cytochemistry Folia Histochem Cytobiol. 2018.